(untitled) (Ciencias de la Ingeniería y Aplicadas, 2021)
In the research, the characterization of the mechanical properties of the clay tiles produced by potters from the La Victoria parish is carried out. The analysis of the chemical composition of the clays, fraction of fine particles, granulometry, liquid limits and the plastic limit was carried out. The compression tests were carried out under ASTM C-42 standards, while the flexural tests were carried out under Ecuadorian INEN 990 standards. From the results obtained, it is concluded that the clay from the Tingo sector has better values ​​in both the plastic index, the liquid and texture limit. The characteristics for the production of the tile are identified, as it is a clay soil, where there is a greater resistance to bending, resulting in 471 N.